A highly diverse spectrum of naphthoquinone derivatives produced by the endophytic fungus Biatriospora sp. CCF 4378 - Stodůlková, Eva; Man, Petr; Kuzma, Marek; Černý, Jan; Císařová, Ivana; Kubátová, Alena; Chudíčková, Milada; Kolařík, Miroslav; Flieger, Miroslav (Folia microbiologica, 2015)
A strain of Biatriospora sp. CCF 4378 was tested for the production of secondary metabolites under submerged fermentation conditions. Eleven compounds were isolated from the culture broth, and the structures of these compounds were determined using HRMS, NMR and X-ray analysis. In addition to six known naphthoquinone derivatives, i.e. ascomycone A, ascomycone B, 6-deoxyfusarubine, 6-deoxyanhydrofusarubine, herbarine and balticol A, one derivative of 2-azaanthraquinone, 6-deoxybostrycoidine, was also identified. Four new natural pyranonaphthoquinones were found, and these natural products were pleorubrin A, pleorubrin B, pleorubrin C and pleorubrin D. The toxicity on human cell lines of the crude naphthoquinone fraction and pure 6-deoxybostrycoidin, ascomycone B, pleorubrin B and 6-deoxyfusarubin was tested. Ascomycone B and 6-deoxyfusarubin elicited rapid cytotoxicity at micromolar concentrations.
Keywords: molekulární struktura; endofyty; buněčné linie; Ascomycota; Molecular Structure; Naphthoquinones; viabilita buněk; Cell Line; Ulmus; Cell Survival; lidé; naftochinony; Humans; Endophytes